TRIPLE BOTTOM LINE DAN SUSTAINABILITY - Felisia .; Amelia Limijaya (Bina Ekonomi, 2014)
Triple Bottom Line (TBL) concept is increasingly being used by organisations to report on how they  respond to sustainability issues.  TBL should consist of three measurement elements, namely: financial, social, and environmental. TBL should be interpreted as a relative concept that is dynamic and iterative. Continuous monitoring needs to be performed in order for organisations to be able to continuously adapt themselves to the changes that might happen in the marketplace as well as society.